Design and Implementation of a File Encryption System Based on Object-Oriented Programming Using C++ - Jimmy, Jimmy` (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Data security has become a critical aspect in the digital era, especially in protecting confidential files from unauthorized access. This study aims to design and implement a file encryption system based on Object-Oriented Programming (OOP) principles using the C++ programming language. The system is developed by applying the core concepts of OOP, namely encapsulation, inheritance, and polymorphism, to create a modular and reusable software architecture. The encryption process is implemented using symmetric key algorithms, allowing users to encrypt and decrypt text-based files securely. The program design follows a layered class structure, where each class handles specific functionalities such as key generation, file reading and writing, and cryptographic operations. The implementation is conducted in a console-based environment with a focus on simplicity, efficiency, and maintainability of the source code. The evaluation results show that the OOP-based approach enhances the flexibility of system modification and reduces code redundancy compared to traditional procedural programming. Furthermore, performance testing demonstrates that the encryption and decryption processes can be executed efficiently without significant latency for small to medium-sized files. This research concludes that applying OOP concepts in C++ provides a structured and scalable framework for developing secure and maintainable encryption systems, which can be further enhanced for larger-scale or GUI-based applications in the future.